Myth, Meaning, and the Work of Life: Enuma Elish and the Garden of Eden (Genesis 2:4–3:24) on the Value of Human Labor and Memory - Balogh, Amy L. (Religions, 2022)
This article offers a new comparison of the ancient Mesopotamian story Enuma Elish and the biblical Garden of Eden story (Genesis 2:4–3:24) as a case study that demonstrates how attention to myth theory and comparative method might improve studies of ancient Southwest Asian literatures. This comparison illustrates the connection between myth, meaning making, and the lived experiences that produced and perpetuated these myths by focusing on the cultural value of work and memory as expressed in both narratives. In contrast to previous modes of comparison that conclude with claims to the Bible’s superiority, this comparison uses tools from myth studies and comparative religion toward a clearer understanding of the cultural messaging of both myths regarding the purpose of human life.